Bilingualism, Trilingualism, Multilingualism, and Polylingualism: Softening Language Boundaries in South African Classrooms. - Kemende Wunseh, Quinta (Linguistic, English Education and Art (LEEA) Journal, 2024)
ABSTRACT South African society is highly diverse with 12 official (including the South African sign language) languages used for teaching and learning. This society is multilingual, multicultural, and multireligious. Translanguaging is simply a pedagogical term used to describe the natural ways bilingual/multilingual individuals use their languages in their everyday lives. This paper suggests translanguaging pedagogy to soften language boundaries in South African multilingual and multicultural classrooms. Hence, educators working with multilingual learners must remember that a positive teaching foundation translates across language barriers. This paper is discussed qualitatively using an extended literature review examining both national and international studies that are relevant to the topic. These sources were identified and analysed. The result from this extended literature review shows that translanguaging goes beyond theory to critical pedagogical practice. Also, it shows that effective teaching strategies based on empathy and acceptance should easily translate from monolingual to multilingual learners. Therefore, there is a need to employ a translanguaging strategy in the classroom to center the marginalised languages in South African classroom space. This extended literature review offers a prototype for teachers, education actors, and policymakers to re-imagine South Africa’s bi/multilingual classrooms through the lens of translanguaging. Keywords: Bi/Multilingualism, Extended Literature, South Africa; Translanguaging